Enabling Proof-of-Work for Low-End IoT Devices - Bartolomeu, Paulo C. (2020)
Cyber-physical housing technology is going through a revolution, started the early 2000s and expected to continue in the years to come. In fact, according to market research reports, connected devices for smart homes will soon have the largest market share of all IoT devices. In contrast with siloed devices and applications, which until recently prevailed even in the most sophisticated dwellings, nowadays it is already possible to glimpse a complex blend of technologies seamlessly integrated to promote the residents' comfort. However, several challenges lie ahead before the technology can fully support such a visionary scenario. One of them is security, especially in scenarios encompassing low-end embedded devices. This paper describes a mechanism allowing limited resource embedded appliances to participate in a network of IoT devices secured by a distributed ledger technology named IOTA. The paper describes the devised proof-of-concept implementation and provides insight on preliminary performance results showing its feasibility.